1
$\begingroup$

Solve for $\textbf{x}(t)$ from the system of differential equations $\textbf{x}' (t) = A \textbf{x}(t)$, where

$$ A =\begin{bmatrix} 0 & -1 & 0\\1 & 0 & 0\\ 0 & 0 & 1\\\end{bmatrix}$$

I did the following:

I found the characteristic polynomial, $|A - \lambda I| = (1-\lambda)(\lambda^2 +1) = 0$, thus $\lambda_1 = 1, \lambda_2 = i, \lambda_3 = -i$.

Now, for $\lambda_1$ the corresponding eigenvector is $\textbf{v}_1 = \begin{bmatrix} 0\\ 0\\ 1 \end{bmatrix}$

For $\lambda_2$ the corresponding eigenvector is $\textbf{v}_2 = \begin{bmatrix} 1\\ -i\\ 0 \end{bmatrix}$

For $\lambda_3$ the corresponding eigenvector is $\textbf{v}_3 = \begin{bmatrix} 1\\ i\\ 0 \end{bmatrix}$

Thus $V = \begin{bmatrix} 0 & 1 & 1\\ 0 &-i & i\\ 1 &0 &0 \end{bmatrix}$

Next, I want to use this: $c_1 e^{\lambda_1 t}\textbf{v}_1 + c_2 e^{\lambda_2 t}\textbf{v}_2 + c_3 e^{\lambda_3 t}\textbf{v}_3$.

\begin{align}

\textbf{x}(t) &= c_1 e^{\lambda_1 t}\textbf{v}_1 + c_2 e^{\lambda_2 t}\textbf{v}_2 + c_3 e^{\lambda_3 t}\textbf{v}_3\

\textbf{x}(t) &= c_1 e^{t}$\begin{bmatrix} 0\\ 0\\ 1 \end{bmatrix}$ + c_2 e^{i t}$\begin{bmatrix} 1\\ -i\\ 0 \end{bmatrix}$ + c_3 e^{-i t}$\begin{bmatrix} 1\\ i\\ 0 \end{bmatrix}$

\end{align}

$\endgroup$
  • 1
    $\begingroup$ See this and this. $\endgroup$ – Git Gud Nov 4 '14 at 19:23
  • 1
    $\begingroup$ I will post what I have tried so far as soon as I type it up. Windows made me restart before I got the chance. $\endgroup$ – GaMbiTaaaa Nov 4 '14 at 20:11
1
$\begingroup$

The solution is $x(t)=\exp(tA) x(0)=V\exp(tD)V^{-1} x(0)$ where $$\exp(tD)=\begin{pmatrix}e^t&0&0\\0&e^{it}&0\\0&0&e^{-it}\end{pmatrix}$$

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

You have found that $$ A = V\left[\begin{array}{ccc}1 & 0 & 0 \\ 0 & i & 0 \\ 0 & 0 & -i\end{array}\right]V^{-1}. $$ Because $V$ is a constant matrix, the equation can be written as $$ \frac{d}{dt}(V^{-1}x(t))= \left[\begin{array}{ccc}1 & 0 & 0 \\ 0 & i & 0 \\ 0 & 0 & -i\end{array}\right](V^{-1}x(t)). $$ Therefore, $$ V^{-1}x(t) = \left[\begin{array}{c}ae^{t} \\ be^{it} \\ ce^{-it}\end{array}\right] $$ where $a$, $b$, $c$ are arbitrary constants. Solving for $x(t)$ gives $$ x(t) = V\left[\begin{array}{c}ae^{t} \\ be^{it} \\ ce^{-it}\end{array}\right] = ae^{t}{\bf v_{1}}+be^{it}{\bf v_2}+ce^{-it}{\bf v_3}. $$

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

Answer. $$ {\boldsymbol{x}}(t)=\mathrm{e}^{tA}{\boldsymbol{x}}(0), $$ where $$ \mathrm{e}^{tA}=\left(\begin{matrix} \cos t&-\sin t& 0\\ \sin t & \,\,\,\,\cos t & 0 \\ 0 & 0 &\mathrm{e}^t \end{matrix}\right). $$

Professional advice. Do not diagonalise this particular matrix $A$. It is much easier, for this one, to simply write down what its exponential is.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.